Discourse Structure and Code Types in Friday Sermons in Tegal Regency, Central Java - Taryono, Mohamad Rizal; Rustono, Rustono; Joko Santoso, Bernadus Wahyudi (Universitas Negeri Semarang, 2023)
The Friday Sermon (Kh.J) as an oral discourse has a distinctive discourse structure because it consists of two discourse parts, each with its own structure. Additionally, Kh.J is a unique monologue discourse because the speakers in the Friday sermon are two individuals, the preacher (khatib) and the caller to prayer (muazin). This study aims to discover and analyze the discourse structure and code types in Kh.J in Tegal Regency, Central Java. The data collection techniques used in this study are recording technique, simak bebas libat cakap technique (SBLC), and note-taking technique. Meanwhile, referential equivalence method and marking analysis technique are used for data analysis. Based on the results of the data analysis, the following conclusions can be drawn. The discourse structure of Kh.J in Tegal Regency, Central Java, consists of two discourse parts that form a complete discourse, namely the first Kh.J and the second Kh.J. The structure of the first Kh.J includes opening greetings, azan, tahmid, syahadat, selawat, wasiat takwa, speech of greetings, recitation of the Qur’an or hadis, hopes, and prayers. On the other hand, the structure of the second Kh.J consists of tahmid, syahadat, selawat, wasiat takwa, and closing prayer. The codes used in the Kh.J discourse in Tegal Regency, Central Java, include the Indonesian code in the form of the Bahasa Indonesia and the Arabic code in the form of the Arabic language.